2014
DOI: 10.1371/journal.pone.0084965
|View full text |Cite
|
Sign up to set email alerts
|

Facial Mimicry in 6–7 Year Old Children with Disruptive Behavior Disorder and ADHD

Abstract: BackgroundImpairments in facial mimicry are considered a proxy for deficits in affective empathy and have been demonstrated in 10 year old children and in adolescents with disruptive behavior disorder (DBD). However, it is not known whether these impairments are already present at an earlier age. Emotional deficits have also been shown in children with attention-deficit/hyperactivity disorder (ADHD).AimsTo examine facial mimicry in younger, 6–7 year old children with DBD and with ADHD.MethodsElectromyographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…An important question is whether these difficulties are present from the onset, or a secondary consequence of atypical social interaction arising from frequent conduct problems. Relevant to this question and to our review, automatic facial mimicry in response to emotional expressions appears typical in 6–7‐year olds with ADHD (Deschamps, Munsters, Kenemans, Schutter, & Matthys, ). Intriguingly, studies have failed to establish impairments in establishing secure attachment in ASD (Rutgers, Bakermans‐Kranenburg, van Ijzendoorn, & van Berckelaer‐Onnes, ), while insecure attachment has been frequently associated with ADHD (Storebo, Rasmussen, & Simonsen, ).…”
Section: Review Of the Literaturementioning
confidence: 84%
“…An important question is whether these difficulties are present from the onset, or a secondary consequence of atypical social interaction arising from frequent conduct problems. Relevant to this question and to our review, automatic facial mimicry in response to emotional expressions appears typical in 6–7‐year olds with ADHD (Deschamps, Munsters, Kenemans, Schutter, & Matthys, ). Intriguingly, studies have failed to establish impairments in establishing secure attachment in ASD (Rutgers, Bakermans‐Kranenburg, van Ijzendoorn, & van Berckelaer‐Onnes, ), while insecure attachment has been frequently associated with ADHD (Storebo, Rasmussen, & Simonsen, ).…”
Section: Review Of the Literaturementioning
confidence: 84%
“…Whatever the cause, present data are rather explicit in telling that sex differences in such capacities are already expressed in the age bracket of the present study and therefore they are of considerable value at least at a methodological level. RFRs are being increasingly used to test pathogenetic hypotheses on neurodevelopmental disorders (McIntosh et al, 2006 ; Press et al, 2010 ; Deschamps et al, 2014 ), and are therefore increasingly used in pediatric populations. The original finding of sex differences in RFRs in adults (Thunberg and Dimberg, 2000 ) greatly influenced the selection of experimental populations in the subsequent literature.…”
Section: Discussionmentioning
confidence: 99%
“…Males produce RFRs of smaller amplitude than females, possibly due to the greater female parental investment and empathy compared with males. RFRs have been recorded in children (McIntosh et al, 2006 ; Beall et al, 2008 ; Oberman et al, 2009 ; Deschamps et al, 2012 , 2014 ; Geangu et al, 2016 ). A very large and recent web-based study confirmed sex differences in facial reactions to affective stimuli, and suggested that the differences between sexes could not be entirely quantitative (females more than males).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that one of the main regions involved in the inhibitory control is also responsible for anger mimicry, we could assume that individuals with ADHD present difficulties in facial mimicry, which would hamper their ability to simulate and infer emotions of others. But, so far, only one study has investigated the relationship between ADHD and facial mimicry ( 124 ), and it found no association between both. However, we must consider that the age group of participants were very limited (6–7 years old), and differences might have been undetectable due to their development stage, which highlights the need for further studies.…”
Section: Facial Mimicrymentioning
confidence: 99%